2018
DOI: 10.1002/hep.30113
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Architecture of Diet‐Induced Hepatic Fibrosis in Mice

Abstract: We report the genetic analysis of a "humanized" hyperlipidemic mouse model for progressive nonalcoholic steatohepatitis (NASH) and fibrosis. Mice carrying transgenes for human apolipoprotein E*3-Leiden and cholesteryl ester transfer protein and fed a "Western" diet were studied on the genetic backgrounds of over 100 inbred mouse strains. The mice developed hepatic inflammation and fibrosis that was highly dependent on genetic background, with vast differences in the degree of fibrosis. Histological analysis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 35 publications
3
79
0
Order By: Relevance
“…This indicates that analysis of the expression of fibrosis marker genes can be used for monitoring the progression of NAFL to NASH. Similar results of early upregulation fibrosis marker genes, including Col1a1 and Tnf , and a high Krt8/Krt18 ratio were observed in a diet‐induced mouse model of hepatic fibrosis 18 and in a Krt18 −/− transgenic mouse model of NASH 31 …”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This indicates that analysis of the expression of fibrosis marker genes can be used for monitoring the progression of NAFL to NASH. Similar results of early upregulation fibrosis marker genes, including Col1a1 and Tnf , and a high Krt8/Krt18 ratio were observed in a diet‐induced mouse model of hepatic fibrosis 18 and in a Krt18 −/− transgenic mouse model of NASH 31 …”
Section: Discussionsupporting
confidence: 64%
“…Unfortunately, the study does not interrogate the impact of genetic differences within a genetically diverse population for the development of NAFLD due to insufficient genetic diversity in this model. To address this limitation, several studies have used a population‐based approach to investigate the molecular pathogenesis of NAFLD induced by obesogenic high‐fat and high‐sucrose (HF/HS) diets in the Hybrid Mouse Diversity Panel (HMDP) 16,17 or BXD recombinant strains 18 . These studies have identified fundamental molecular phenotypes and metabolic and transcriptomic pathways associated with the development and progression of NAFLD; however, the role of sex‐specific alterations that contribute to the pathogenesis of human NAFLD 19 remained unanswered because only male mice were used 16‐18 …”
Section: Introductionmentioning
confidence: 99%
“…The current study elegantly demonstrated the importance of mouse strains by feeding a Western diet to over 100 mouse strains. Mice that developed steatosis or NASH with fibrosis varied greatly across strains, such as HMDP mice developing HS without fibrosis and BXD19/Ty mice developing hepatic fibrosis …”
mentioning
confidence: 76%
“…Although current preclinical NAFLD models can be considered indispensable tools for studying chronic liver disease pathology, it should be noted that the majority of existing rodent models mainly focus on certain stages of the disease rather than the total spectrum. Additionally, it is noteworthy that the NAFLD disease progression greatly varies across different strains [140]. Therefore, depending on its research question, careful model selection is highly recommended.…”
Section: Discussionmentioning
confidence: 99%